Criticality Evaluation To Support Maintenance Management of Manufacturing Systems - Lopes, Isabel; Figueiredo, Miguel; Sá, Vera (International Journal of Industrial Engineering and Management, 2020)
This paper focuses on criticality evaluation for supporting daily equipment maintenance management and the definition of medium and long-term maintenance actions to improve equipment and, therefore, productivity. These two different purposes led to the development of two different methods for criticality evaluation, using criteria adjusted for each case. The first method is based on rules for defining priorities for corrective and preventive mainte- nance tasks. Since a failure mode of critical equipment is not necessarily critical, priorities for maintenance tasks are assigned to tasks rather than to equipment. The second method uses Analytic Hierarchy Process to prioritize equipment based on its performance. This method is based on the indicators commonly monitored by maintenance departments. In addition to assessing equipment performance, it considers the maintenance effort made to achieve the evaluated performance. The selection of the criticality criteria and the development of the methods was based on literature review and triggered by a case study in a multination- al automotive company. With the integration of the proposed methods in a computerized maintenance management system, maintenance technicians and managers are able to know in real time the tasks that should be performed first and to monitor the overall performance of equipment in the plant, focusing improvements where they are more required. Article history: Received (June 13, 2019); Revised (October 25, 2019); Accepted (October 30, 2019); Published online (November 13, 2019)